2010
DOI: 10.1007/s12070-010-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

The Location of Maxillary Sinus Ostium and Its Clinical Application

Abstract: The endoscopic sinus surgeons must have a detailed knowledge of inconsistent location of maxillary sinus openings in any interventional maxillary sinus surgeries as it relates to the orbital floor, ethmoid infundibulum and the nasolacrimal duct. Forty cadaver head and neck specimens had been cut sagittally through the nose, such that the lateral nasal wall had been preserved. The findings were documented with an emphasis on location of the maxillary sinus openings. In the present study maxillary sinus ostium o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 3 publications
3
43
0
Order By: Relevance
“…But Rice and schaeffer [24] termed all extra openings other than a single primary maxillary ostium as accessory maxillary ostium irrespective of their location. Prasanna [25] in his study on forty cadavers head & neck specimens cut sagittally through the nose reported accessory…”
Section: Discussionmentioning
confidence: 99%
“…But Rice and schaeffer [24] termed all extra openings other than a single primary maxillary ostium as accessory maxillary ostium irrespective of their location. Prasanna [25] in his study on forty cadavers head & neck specimens cut sagittally through the nose reported accessory…”
Section: Discussionmentioning
confidence: 99%
“…Another study used the punctum subnasale as their pivot landmark, the distance from this point on the upper lip to maxillary orifice in the area of hiatus semilunaris was recorded as 48.25 ± 0.75 mm at an angle of 30° (Djambazov, ). Similar studies have sought to pin‐point the maxillary sinus ostia within the hiatus semilunaris (Van Alyea, ; Stammberger, ; Prasanna and Mamatha, ). Prasanna and Mamatha () found that in a majority (52.5%) of specimens, the ostium was located within the posterior 1/3 of the hiatus semiluaris.…”
Section: Introductionmentioning
confidence: 97%
“…For reasons discussed above, the superior position of the MSO is arguably a factor contributing to high incidences of MS pathology among humans (Souza et al, 2016). While numerous studies have investigated the frequency of MS pathology (Ikeda, 1996;Perloff et al, 2000;Sánchez Fernández et al, 2000;Slavin et al, 2005;Roberts, 2007) and the position of the MSO relative to specific nasal landmarks for surgical purposes (Myerson, 1932;Van Alyea, 1936;Prasanna and Mamatha, 2010;Souza et al, 2016), few studies have systematically investigated how variations in MS size and/or shape relate to MSO position (an exception being Souza et al, 2016, see below). While human MSs are often described as pyramidal in shape, with the medial wall acting as the base of the pyramid and its apex extending laterally toward the zygoma (Skillern, 1923;Amedee, 1993;Singh and Tabaee, 2016;Souza et al, 2016), the size and shape of the MS are extremely variable at both the population (Shea, 1977;Fernandes, 2004b;Holton et al, 2013;Butaric, 2015;Butaric and Maddux, 2016;Maddux and Butaric, 2017) and individual levels (Anagnostopoulou et al, 1991;Amedee, 1993;Miller and Amedee, 1997;Uchida et al, 1998;Kim et al, 2002;Fernandes, 2004a).…”
Section: Introductionmentioning
confidence: 99%